Dynamic governance of energy technology change. Socio-technical transitions towards sustainability - (:unkn) unknown (Springer, 2013)
Formulating effective responses to the global challenges of mitigating climate change and securing a sustainable energy future requires a clear understanding of the interdependent causalities between institutions, local decision making, strategic alliances and eco-innovations, as well as policies. It has been acknowledged that the linear "Manhattan project" model is not an adequate governance model for mastering the dynamic complexity of socio-technical transitions; therefore this book aims at advancing research on systematic transition management models. It offers qualitative and quantitative analyses of socio-technical transitions in road transportation and housing, bringing together tailored theorizing on sustainability transitions and applied system dynamics modeling. It highlights the interconnected causal feedbacks that are required to overcome the lock-in situation in road transportation and housing fueled by fossil energies. Showing which concerted actions and framework conditions are required in the transition phases in order to initiate and sustain socio-technical transition, it serves as a guide to model-based strategy making, policy design and analyses in support of sustainable futures.
Keywords: Energie; Energiewirtschaft; Energietechnologie; Technologieeinsatz; Simulation; Innovation; Governance; Akzeptanz; Klimawandel; Klimaschutzpolitik; Technikwandel; Fahrzeugtechnologie; Anpassungsstrategie